Cost-Minimization Analysis of Transcatheter versus Surgical Closure of Secundum Atrial Septal Defect in Children - Poomiporn Katanyuwong (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND Objective: Secundum atrial septal defect (ASD) is one of the congenital heart diseases commonly found in children, which can be treated by transcatheter closure as a standard treatment or by surgical treatment. Few studies have analyzed the cost of these two strategies. The present study is aimed to compare the short-term cost-minimization of both procedures. Materials and Methods: A retrospective single-center study analyzed all children aged 1 to 18 years, diagnosed with isolated secundum atrial septal defect, who were entirely treated by transcatheter or surgical ASD closure at Ramathibodi Hospital, Mahidol University between January 2005 and August 2016. The baseline characteristics, total hospital days, cost per case, clinical outcomes, and complications between these two procedures are compared. Results: Thirty-five patients were enrolled in the present study, divided into two groups, with 43% in the transcatheter group and 57% in the surgical group. The baseline characteristics of the transcatheter and surgical groups were not significantly different except for weight, which was 28.6 kg versus 16.5 kg (p=0.045), and for medical history of asymptomatic, which was seven versus 16 patients (p=0.04), respectively. Patients with transcatheter procedures had a shorter length of hospital stay at 2.3 days versus 8.1 days (p<0.001), respectively. The direct medical cost per case of surgical procedure was less than the transcatheter procedure at 116,993 Baht or 3,878 US Dollar versus 206,204.7 Baht or 6,835 US Dollar (p<0.001), respectively. The major complication of the transcatheter procedure was bleeding from the puncture site while it was intraoperative arrhythmia for the surgical procedure. Conclusion: The short-term clinical outcomes of the transcatheter and the surgical ASD closure were excellent. The cost analysis suggests that surgical procedures may incur fewer costs than transcatheter procedures from the hospital’s perspective. Surgical ASD closure may be a less costly strategy for Ramathibodi pediatric patients.